2021
DOI: 10.1038/s41598-021-92408-4
|View full text |Cite
|
Sign up to set email alerts
|

FIP200 controls the TBK1 activation threshold at SQSTM1/p62-positive condensates

Abstract: The protein kinase TBK1 is a central regulator of innate immune responses and autophagy, and ablation of either function has been linked to neuroinflammatory or degenerative diseases. Autophagy is an intracellular process that recycles old or damaged proteins and organelles. In recent years, the TBK1-dependent regulation of autophagy pathways has been characterized. However, the autophagy-dependent regulation of TBK1 activity awaits further clarification. Here, we observed that TBK1 is recruited to SQSTM1/p62-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Tank binding kinase (TBK1) has recently been implicated in autophagy activation. It is recruited by autophagy receptors to damaged organelles such as mitochondria [ 24 ], aggregates [ 25 ], or lysosomes [ 26 ], leading to their elimination. TBK1 is also involved in the degradation of invasive bacteria by autophagy, following detection of cellular membrane penetration by galectins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tank binding kinase (TBK1) has recently been implicated in autophagy activation. It is recruited by autophagy receptors to damaged organelles such as mitochondria [ 24 ], aggregates [ 25 ], or lysosomes [ 26 ], leading to their elimination. TBK1 is also involved in the degradation of invasive bacteria by autophagy, following detection of cellular membrane penetration by galectins.…”
Section: Introductionmentioning
confidence: 99%
“…Gal8 is also responsible for local activation of TBK1 [ 27 ]. Activated TBK1 promotes the phosphorylation of autophagy receptors including NDP52 [ 27 ], p62 [ 25 ], optineurin [ 28 ] and Tax1BP1 [ 29 ]. Phosphorylation of the receptors is thought to drive sustained autophagy activation [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies including the current manuscript demonstrated TBK1 activation upon FIP200 deletion in different cells 46 , the mechanisms involved are not well understood at present. Our previous studies suggested that FIP200 interaction with a TBK1 adaptor molecule, AZI2, may serve to restrict TBK1 activation in other cells 28 .…”
Section: Discussionmentioning
confidence: 77%
“…This series of events is also sustained by the observation that p62, NBR1, and TAX1BP1 are associated with protein aggregates even in the absence of an intact ATG machinery [57]. In addition, TAX1BP1 recruits the TBK1 kinase to protein aggregates, leading to the phosphorylation of p62, a post-translational modification that enhances p62 binding to Ub [58]. This function appears to be regulated by FIP200 [58], indicating that the recruitment of SARs to aggregates not only guides their recognition by the ATG machinery but also serves for their own feedback regulation to enhance cargo binding and clustering.…”
Section: Box 2 the Mechanism Of Macro-autophagymentioning
confidence: 82%
“…In addition, TAX1BP1 recruits the TBK1 kinase to protein aggregates, leading to the phosphorylation of p62, a post-translational modification that enhances p62 binding to Ub [58]. This function appears to be regulated by FIP200 [58], indicating that the recruitment of SARs to aggregates not only guides their recognition by the ATG machinery but also serves for their own feedback regulation to enhance cargo binding and clustering. In line with the current view of the mechanism of selective types of autophagy (Box 3), p62 bodies are also a platform for autophagosome generation [45].…”
Section: Box 2 the Mechanism Of Macro-autophagymentioning
confidence: 99%